The development and validation on nomination scales for the identification of gifted children - Cabreros, Floraida C. (Education quarterly.)
The purpose of the study is to develop and validate four scales using teachers, parents, peers and gifted children to nominate the intellectually gifted as an identification strategy. The validity of the four scales is sought in terms of content, criterion, construct, convergence and predictors.